BUILDING EMPLOYEE PERFORMANCE THROUGH LEADERSHIP, TRAINING, WORK DISCIPLINE AND JOB SATISFACTION - Tjahjadi, Dicky; Ismuhadjar Ismuhadjar; Alex Zami (Dinasti International Journal of Digital Business Management, 2022)
This study aims to analyze and prove the influence of leadership, training, work discipline and job satisfaction on employee performance. The research method used is descriptive quantitative method, causal approach and explanatory survey with sample size of 316 respondents. Analysis method used Structural Equation Modeling (SEM). The results showed that partially the leadership and training have positive and significant influence on job satisfaction, meanwhile work discipline has positive influence but not significant on toward job satisfaction. The result of first structural equation indicates that simultaneously leadership, training and work discipline have positive and significant influence on job satisfaction with a contribution (R-square value) of 70%. The most dominant variable that affects job satisfaction is leadership. The result of second structural equation either partially or simultaneously leadership, training, work discipline and job satisfaction have positive and significant influence on employee performance with a contribution (R-square value) of 83%. The most dominant variable that affects employee performance is job satisfaction. The result had also shown that job satisfaction is a partial mediating of leadership, training, and work discipline on employee performance.